Rehabilitation of overuse tendon injuries and ligament failures - Lohrer, H.; Alt, W. W.; Gollhofer, A. (Neuromuscular aspects of sport performance, 2011)
This chapter contains sections titled: Introduction, Achilles tendon, Patellar tendinopathy (Jumper's Knee), Ligament, Conclusion, References.